Risk-based decision-making in the treatment of HER2-positive early breast cancer: Recommendations based on the current state of knowledge - Jackisch, Christian; Cortazar, Patricia; Geyer, Charles E.; Gianni, Luca; Gligorov, Joseph; Machackova, Zuzana; Perez, Edith A.; Schneeweiss, Andreas; Tolaney, Sara M.; Untch, Michael; Wardley, Andrew; Piccart, Martine (Cancer treatment reviews, 2021)
Treatment of HER2-positive early breast cancer (EBC) continues to evolve with neoadjuvant (pre-operative) and adjuvant (post-operative) HER2-targeted therapies as standard of care. There are two important decision points. The first involves deciding between neoadjuvant therapy or proceeding directly to surgery. Neoadjuvant chemotherapy (NACT) plus pertuzumab-trastuzumab is appropriate for patients with high-risk HER2-positive EBC (tumour diameter ≥2 cm, and/or node-positive disease). Patients with node-negative disease and tumour diameter <2 cm are candidates for upfront surgery followed by paclitaxel for 12 weeks plus 18 cycles of trastuzumab, with the option to add pertuzumab (if pN+). The second decision point involves the pathohistological result at surgery after neoadjuvant therapy. Total pathological complete response (tpCR: ypT0/is, ypN0) is associated with improved survival endpoints. Patients with tumours ≥2 cm and/or node-positive disease at diagnosis who have a tpCR after dual blockade should continue pertuzumab-trastuzumab in the adjuvant setting to complete 1 year (18cycles) of treatment. For patients with invasive residual disease, 14cycles of post-neoadjuvant trastuzumab emtansine (T-DM1) therapy significantly increases invasive-DFS compared with trastuzumab. Extended adjuvant therapy with neratinib is an option in selected patients (HER2-positive and oestrogen receptor [ER]-positive) who have completed adjuvant trastuzumab-based therapy. Less aggressive chemotherapy regimens are recommended in populations with a lower risk of recurrence (patients with small tumours without axillary involvement; patients unlikely to tolerate anthracycline-taxane or taxane-carboplatin regimens). Ultimately, treatment recommendations should be consistent with local and international guidelines. Further studies will guide optimisation of treatment for patients with HER2-positive EBC according to the risk of disease recurrence.
Gesehen am 28.10.2021